Growth Opportunities and Risk-Taking by Financial Intermediaries - Herring, Richard J.; Vankudre, Prashant (Journal of Finance, 1987)
We show that growth opportunities which cannot be converted to cash under conditions of financial distress ( G z ) are a critical determinant of an intermediary's choice of risk. Financial institutions in which G z is a low proportion of total assets will be much more likely to engage in go-for-broke behavior. The model leads to a reevaluation of the effectiveness of several traditional remedies for dealing with banks that take excessive risks such as raising insurance premiums, intervening before capital is depleted, and restricting investment options. The model also has implications about a new approach to the examination of financial intermediaries.